Penggunaan Kata Roh Sang Hyang Pengardi Sebagai Terjemahan Kata Roh Kudus Dalam Alkitab Bahasa Bali - I Ketut Gede Suparta (Jurnal Teologi Kontekstual Indonesia, 2022)
In the process of translating the word Holy Spirit into the Balinese Bible, there are differences in concepts with the understanding of balinese people in general. Therefore it is necessary to put forward the proper concept of the Holy Spirit in accordance with the correct meaning as the concept of the Bible itself. Thus the author conducted research on the meaning of the word about the Holy Spirit that can be used in the context of the Balinese language so that the meaning in question is actually understood as intended by the Bible itself, so that the translation of the Bible into Balinese does not deviate from the original meaning. The research approach that the authors use is qualitative research. After conducting the analysis, the author found the word Roh Sang Pengardi as a relevant word for the word Holy Spirit. The word Roh Sang Pengardi can actually provide an understanding that is more in accordance with the concept of the Bible. The word describes the creator person, of which the Holy Spirit is the third person of the Trinity who is the creator of the universe. AbstrakDalam proses penerjemahan kata Roh Kudus ke Alkitab bahasa Bali, terdapat perbedaan konsep dengan pemahaman masyarakat Bali pada umumnya. Oleh sebab itu perlu dikemukakan konsep yang tepat tentang Roh kudus sesuai dengan makna yang benar seperti konsep Alkitab itu sendiri. Dengan demikian penulis mengadakan penelitian makna kata tentang Roh Kudus yang dapat dipakai dalam konteks bahasa Bali agar makna yang dimaksud benar-benar dipahami seperti yang dimaksudkan oleh Alkitab itu sendiri, sehingga penerjemahan Alkitab ke dalam bahasa Bali tidak menyimpang dari makna yang asli. Pendekatan penelitian yang penulis gunakan adalah penelitian kualitatif. Setelah melakukan analisis, penulis menemukan kata Roh Sang Hyang Pengardi sebagai kata yang relevan untuk kata Roh Kudus. Kata Roh Sang Hyang Pengardi justru dapat memberikan pemahaman yang lebih sesuai dengan konsep Alkitab. Kata tersebut menggambarkan tentang pribadi pencipta, dimana Roh Kudus adalah pribadi ketiga Tritunggal yang pencipta semesta.